Discogenic Low Back Pain: Anatomy, Pathophysiology and Treatments of Intervertebral Disc Degeneration - Mohd Isa, Isma Liza; Teoh, Seong Lin; Mohd Nor, Nurul Huda; Mokhtar, Sabarul Afian (International journal of molecular sciences, 2022)
Intervertebral disc (IVD) degeneration is a major contributing factor for discogenic low back pain (LBP), causing a significant global disability. The IVD consists of an inner core proteoglycan-rich nucleus pulposus (NP) and outer lamellae collagen-rich annulus fibrosus (AF) and is confined by a cartilage end plate (CEP), providing structural support and shock absorption against mechanical loads. Changes to degenerative cascades in the IVD cause dysfunction and instability in the lumbar spine. Various treatments include pharmacological, rehabilitation or surgical interventions that aim to relieve pain; however, these modalities do not halt the pathologic events of disc degeneration or promote tissue regeneration. Loss of stem and progenitor markers, imbalance of the extracellular matrix (ECM), increase of inflammation, sensory hyperinnervation and vascularization, and associated signaling pathways have been identified as the onset and progression of disc degeneration. To better understand the pain originating from IVD, our review focuses on the anatomy of IVD and the pathophysiology of disc degeneration that contribute to the development of discogenic pain. We highlight the key mechanisms and associated signaling pathways underlying disc degeneration causing discogenic back pain, current clinical treatments, clinical perspective and directions of future therapies. Our review comprehensively provides a better understanding of healthy IVD and degenerative events of the IVD associated with discogenic pain, which helps to model painful disc degeneration as a therapeutic platform and to identify signaling pathways as therapeutic targets for the future treatment of discogenic pain.